Sewaka Dharma Spirit of Effective Public Service Bureaucratic Culture during the Covid-19 Pandemic - I Nengah Merta; Ni Nengah Karuniati; Ni Luh Putu Erma Mertaningrum; I Dewa Nyoman Juniasa; I Gede Putu Yasa; Moch. Noor; I Gde Oka Saputra (International Journal of Social Science and Business, 2022)
The shift in public demands for more effective public services during the Covid-19 pandemic has made public service bureaucracies aware of the need to improve immediately. This study aims to analyze the factors that cause the low performance of public service organizations based on identifying factors and suggesting several operational policies to improve the performance of public service bureaucracies. This type of research is qualitative. The method of collection uses document analysis and references. The technique used to analyze the data is descriptive qualitative analysis. The results of this study show that the service culture is imbued with a monopolistic, patriarchal culture and is constrained by various formal constraints, moving the public service bureaucracy slowly and rigidly. This condition causes the quality of public services to be less than optimal during the Covid-19 pandemic. Government bureaucratic organizations must change their mindset to appear good state servants. Namely, serving is an obligation (sawaka dharma) and not being prestige to carry out their obligations as public servants. The spirit of service is a very relevant obligation to be adopted as a spirit that animates public service practices that can strengthen the government's commitment as a state servant.